Transfer Function Models of Inventory Policies and Bullwhip Quantification in Supply Chain. (2016) - George, Joby; Pillai, V. Madhusudanan
Abstract: Control theory approach to the supply chain is an analytical method to quantify the bullwhip effect. In this study, using control theory approach the bullwhip effect inducing nature of various inventory policies is analyzed. The inventory policies considered are forecast based, forecast + order smoothing, Order-Up-To (OUT), OUT + net stock smoothing + on-order inventory smoothing, and OUT + net stock smoothing + on-order inventory smoothing + order smoothing. The performance measures considered are order rate variance ratio and bullwhip slope. The forecast based policies cause the de-whip effect in the supply chain. The OUT policy and its variants cause bullwhip generation in the supply chain. It is found that the order variance amplification is more under OUT policy than its variants.